Profitability, Fixed Asset Ratio and Business Risk on Capital Structure (Empirical Study on Consumer Goods Industry in the Indonesian Capital Market) - Salwa Ihza Ridwan, Muhammad; Xaverius Situngkir, Daniel; Setiawan, Reza; Ariq Musyaffa, Mughni (International Journal of Psychosocial Rehabilitation, 2020)
Determination of funding sources at the company, should consider the capital structure that is owned. Many factors in determining capital structure include profitability, fixed asset ratio and business risk. This study aims to determine the effect of profitability, fixed asset ratio and business risk on capital structure in the Indonesia Capital Market period 2017-2019. The study used panel data analysis, with a number of samples based on purposive sampling of 30 research samples. Data analysis techniques using multiple linear regression models with the classical assumption test first. Research findings prove that profitability has an influence on capital structure, while fixed asset ratios and business risk have no effect on capital structure. From the exposure of the study it can be concluded that to increase the capital structure can be done by increasing profitability and fixed asset ratios, as well as reducing business risks that occur.